From neuro-immune command circuits to microbiota-mediated regulation in the gastrointestinal tumor microenvironment - Chen, Yuhan; Tang, Dong (Frontiers in Immunology, 2026)
The nervous system plays a profound role in human health and disease, particularly in regulating cancer development through immune system interactions. The enteric nervous system (ENS), often referred to as the “second brain,” comprises millions of neurons and glial cells specialized for the gastrointestinal tract. This system is intimately involved in the growth, infiltration, and metastasis of gastrointestinal tumors. Furthermore, the ENS establishes a bidirectional communication network with the central nervous system via the vagus nerve and spinal afferent nerves, mediating interactions between gut microbiota, the immune system, and the nervous system. Emerging fields like “neuro-immuno-oncology” have introduced neuroimmunomodulatory drugs into clinical practice, but most research focuses on intestinal inflammation, leaving a gap in systematic understanding regarding gastrointestinal tumors. This review systematically summarizes the bidirectional regulatory mechanisms of neuro-immune interactions in gastrointestinal tumors and explores the interplay between nerves, immunity, and microbiota in the gastrointestinal tumor microenvironment. Its aim is to provide a new perspective for understanding the neuro-immune ecology of gastrointestinal tumors and to lay a theoretical foundation for developing cross-scale precision treatment strategies.